Ileal pouch–anal anastomosis with fluorescence angiography: a case‐matched study. (2nd April 2019) - Spinelli, A.; Carvello, M.; Kotze, P. G.; Maroli, A.; Montroni, I.; Montorsi, M.; Buchs, N. C.; Ris, F.
Abstract: Aim: An anastomotic leak in ileoanal pouch surgery may lead to pouch failure. Constructing a tension‐free ileal pouch–anal anastomosis (IPAA) reduces this risk but can be technically challenging, balancing pouch vascularization with ileal mesenteric length and site of vessel ligation. Fluorescence angiography (FA) may help the clinician make a more balanced judgement. Methods: Thirty‐two patients undergoing minimally invasive completion proctectomy with FA‐guided IPAA at two academic centres were matched and compared on a 1:1 basis to a historical group undergoing the same procedure without the use of this technique. Results: Ligation of the ileocolic vessels was safely performed in 15/32 (47%) of FA patients compared with 5/32 (16%) of historical controls. One patient underwent intra‐operative IPAA reconstruction after FA detected ischaemia. No anastomotic leak occurred with FA but there was only one in the historical controls ( P  = 0.31). The postoperative complication rate was similar between the two groups ( P  = 0.60). Conclusion: FA is applicable to IPAA surgery and may help to reduce perfusion‐related anastomotic leaks. A prospective randomized trial is warranted.